The impact of hard infrastructure on bilateral trade flows in selected ASEAN countries - Mohd Mahyideen, Jamilah; Ismail, Normaz Wana; Law, Siong Hook (School of Social Sciences, Universiti Sains Malaysia, 2012)
Trade facilitation has gained more attention in a recent trade research area and has become more important trade policy measures particularly after trade liberalization reform takes place. Trade liberalization has resulted in a significant tariff reduction in most of the countries including ASEAN countries. This has forced ASEAN countries to shift their focus of trade policy towards trade facilitation in order to reduce trade cost and remain as a highly competitive region. Trade facilitation is considered to be a tool that reduces transaction costs and the complexity of international trade and enhances the trading environment. Therefore, with the absence of direct policy barriers, other components of trade cost such as transportation costs and border related trade cost must be reduced. The development of trade-related infrastructure, which is one of the forms of trade facilitation, is therefore very important for ASEAN to capitalize the benefits of international trade. The present study examines the impact of hard infrastructure on bilateral trade flows in selected ASEAN countries over the period 1995-2010 using fixed effect estimator. Some alternative measures for hard infrastructure from transport and ICT sectors are included in this study. Results from a gravity model and bilateral trade data suggest that bilateral trade in ASEAN countries is significantly influence by hard infrastructure.